Temperature Analysis in the Heated Region of the Chamber Electric Furnace of Resistance; AIP Conference Proceedings; Vol. 2212 : Thermophysical Basis of Energy Technologies (TBET 2019) - Naumkin A. S. Aleksandr; Borisov B. V. Boris Vladimirovich; Syrodoy S. V. Semen Vladimirovich; Malishev D. Yu. Dmitry (2020, 2020)
Title screen